An Analysis of Students Reading Comprehension on Students Reading Aloud Activities at the XI Grade of MAN 1 Solok Selatan - Neneng Safitri; Merry Prima Dewi; Hilma Pami Putri; Loli Safitri (Education Achievement: Journal of Science and Research, 2024)
Students' ability in reading, especially reading comprehension is still low. The first problem most of students have limited vocabulary in English, The second problem is that the teacher still uses the conventional strategies in class in reading comprehension. The third problem is students are not able to understand the words conveyed by the teacher orally in English. The purpose of this research was to find out student’s reading comprehension on student’s reading aloud activities at the XI Grade of MAN 1 Solok Selatan. Then, the researcher used descriptive quantitative method. In the collecting the data, test wich consisted of reading comprehension through students reading aloud activities. The data was analyzed by using T- Test Formula. Based on results shows that that 3 students get the score between 95 - 100. That 2 students get the score between 83 - 94. Then 13 students get score between 71 – 82. Then 5 students get the score between 59 – 70. Then 2 students get the score 47 – 58 and 7 students get the score between 35 – 46. In conclusion, the students reading comprehension on reading aloud activities at the XI.IPS.1 students at MAN 1 Solok Selatan was considered medium. Evidenced from when students reading aloud activities the students still confused, and not confidence.